ProFit‐1D—A 1D fitting software and open‐source validation data sets. Issue 6 (13th August 2021) - Borbath, Tamas; Murali‐Manohar, Saipavitra; Dorst, Johanna; Wright, Andrew Martin; Henning, Anke
Abstract : Purpose: Accurate and precise MRS fitting is crucial for metabolite concentration quantification of 1 H‐MRS spectra. LCModel, a spectral fitting software, has shown to have certain limitations to perform advanced spectral fitting by previous literature. Herein, we propose an open‐source spectral fitting algorithm with adaptive spectral baseline determination and more complex cost functions. Theory: The MRS spectra are characterized by several parameters, which reflect the environment of the contributing metabolites, properties of the acquisition sequence, or additional disturbances. Fitting parameters should accurately describe these parameters. Baselines are also a major contributor to MRS spectra, in which smoothness of the spline baselines used for fitting can be adjusted based on the properties of the spectra. Three different cost functions used for the minimization problem were also investigated. Methods: The newly developed ProFit‐1D fitting algorithm is systematically evaluated for simulations of several types of possible in vivo parameter variations. Although accuracy and precision are tested with simulated spectra, spectra measured in vivo at 9.4 T are used for testing precision using subsets of averages. ProFit‐1D fitting results are also compared with LCModel. Results: Both ProFit‐1D and LCModel fitted the spectra well with induced parameter and baseline variations. ProFit‐1D proved to be more accurate than LCModel for simulated spectra. However, LCModel showed a somewhat increased precision for some spectral simulations and for in vivo data. Conclusion: The open‐source ProFit‐1D fitting algorithm demonstrated high accuracy while maintaining precise metabolite concentration quantification. Finally, through the newly proposed cost functions, new ways to improve fitting were shown.